2018
DOI: 10.1093/annonc/mdy483.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of entrectinib in patients with NTRK fusion-positive tumours: Pooled analysis of STARTRK-2, STARTRK-1, and ALKA-372-001

Abstract: Adverse events were mostly low grade. The most common grade 3 toxicities with olaparib were anaemia (22%) and neutropenia (8%). Olaparib dose reductions, interruptions and discontinuations occurred in 28%, 52% and 12%, respectively. There was no approximately 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 0 publications
0
43
0
5
Order By: Relevance
“…The intracranial ORR was 55% in both ROS1-positive NSCLC patients and NTRK fusion-positive solid tumor patients. The median duration of response ranged from 12.6 to 24.6 months [36,37]. DS-6051b is a TKI with high affinity for ROS1 and NTRK kinases/In a phase I/Ib trial, it was found to be well tolerated and had a signal of inhibitory activity.…”
Section: Ntrkmentioning
confidence: 99%
“…The intracranial ORR was 55% in both ROS1-positive NSCLC patients and NTRK fusion-positive solid tumor patients. The median duration of response ranged from 12.6 to 24.6 months [36,37]. DS-6051b is a TKI with high affinity for ROS1 and NTRK kinases/In a phase I/Ib trial, it was found to be well tolerated and had a signal of inhibitory activity.…”
Section: Ntrkmentioning
confidence: 99%
“…A ROS1 ‐receptor tyrosine kinase gene rearrangement occurs in 1% to 2% of patients who have NSCLC, and approximately 36% of these patients present with BMs. First‐line therapies include crizotinib and ceritinib, and entrectinib recently gained US Food and Drug Administration approval, although evidence of intracranial activity of these agents in this patient population is limited, and CNS‐only disease progression rates on crizotinib are as high as 63% . Patients experiencing CNS disease progression on crizotinib should be considered for upfront BM‐directed therapy.…”
Section: Systemic Treatment Of Brain Metastasesmentioning
confidence: 99%
“…First-line therapies include crizotinib and ceritinib, and entrectinib recently gained US Food and Drug Administration approval, although evidence of intracranial activity of these agents in this patient population is limited, and CNS-only disease progression rates on crizotinib are as high as 63%. 39,40 Patients experiencing CNS disease progression on crizotinib should be considered for upfront BM-directed therapy. In the setting of extensive extracranial disease, however, initiating lorlatinib with close surveillance can be considered because there is evidence of intracranial activity in this setting.…”
Section: Anaplastic Lymphoma Kinase and Ros1 Translocationsmentioning
confidence: 99%
“…Tropomyosin receptor kinase (TRK) inhibitors have been reported to be useful for patients with solid tumors harboring neurotrophic receptor tyrosine kinase (NTRK) fusion genes. At the 2018 Annual Meeting of the European Society of Clinical Oncology (ESMO), the results from an integrated analysis of three studies (STARTRK-2 study, STARTRK-1 study and ALKA-372-001 study) conducted in patients with tumors harboring NTRK fusion genes were presented [49]. In these studies, entrectinib, a TRK inhibitor, was administered to 54 patients with soft-tissue sarcomas, non-small cell lung cancer, and others, and the response rate was 57.4%.…”
Section: Chemotherapy For Metastatic Pancreatic Cancermentioning
confidence: 99%